Epidemiology of rosacea in Colombia (2020)
Prevalence of rosacea has been estimated around the world in the range of 0–22%. In Colombia, the prevalence of rosacea remains unknown. The aim of this study was to determine the prevalence of rosacea and the frequencies of its subtypes in Colombia. This cross‐sectional, multicenter study was conducted in six outpatient dermatology clinics across Colombia. A total of 33 dermatologists conducted a comprehensive medical history and physical examination for all rosacea patients seen at their offices over the course of 2 months. All patients who accepted to participate were encouraged to answer a survey about the history of their illness. Of 10,204 outpatients evaluated for rosacea between July and August 2014, 291 rosacea patients were included in this study. The prevalence of rosacea subtypes in this cohort was: 45.3% erythematotelangiectatic (ETR) (n = 132), 48.7% papulopustular (PPR) (n = 142), 4.8% phymatous (n = 14), and 1% ocular (n = 3). Overall, the prevalence in Colombia was 2.85%. Our data represent an important first step to understanding the current state of rosacea in Colombia. The prevalence of rosacea in Colombia is the highest in Latin America among a few reports published, which might be explained by geographic features. However, contrary to our expectations, the prevalence is lower than that in some European countries. We postulate that this finding may be due to methodological differences.